Psychometric properties of the Online Gaming Addiction Questionnaire - Potembska, Emilia; Pawłowska, Beata (Current Problems of Psychiatry, 2015)
This article describes the psychometric properties of the Online Gaming Addiction Questionnaire (KBGUI). An original version of KBUGI, consisting of 130 items, was used to survey a group of 576 adolescents aged 16 to 19 years, inhabitants of the Lublin Province. On the basis of factor analysis, four factors (scales) were identified: (1) Loss, (2) Entertainment and search for new stimuli, (3) Compensation and escape, (4) Violence and domination. Items with the lowest factor loadings and the lowest factor specificity indexes were rejected. The factors identified explained 54% of the total variance. The final version of the KBGUI questionnaire consisted of 74 questions. The coefficients of reliability for the individual scales were high: Cronbach’s alpha = 0.98 for Loss, Cronbach’s alpha = 0.93 for Entertainment and search for new stimuli, Cronbach’s alpha = 0.89 for Compensation and escape, and Cronbach’s alpha = 0.83 for Violence and domination. The reliability coefficient for the global KBUGI score was 0.97. The KBUGI questionnaire is a reliable instrument with good psychometric properties which can be used to asses different dimensions of addiction to Internet games.